Targeting Signal 3 Extracellularly and Intracellularly in Graft-Versus-Host Disease - Kim, Stephanie; Reddy, Pavan (Frontiers in Immunology, 2020)
Allogeneic hematopoietic stem cell transplantation (allo-HCT) holds curative potential for many hematological disorders. However, the pathophysiology of the desired graft-versus-tumor effect is linked to life-threatening complications of acute graft-versus-host disease (GVHD). Allogeneic donor T lymphocytes are essential for causing GVHD, and their activation relies on the coordination of TCR engagement and co-stimulation, also known as Signal 1 and Signal 2. In addition to these signals, a network of secreted cytokines by immune cells provides a third signal, Signal 3, that is critical for the initiation and maintenance of GVHD. Strategies to target Signal 3 in human diseases have shown therapeutic benefit for inflammatory disorders such as Rheumatoid Arthritis and Inflammatory Bowel Disease. However, despite our growing understanding of their role in GVHD, the success of targeting individual cytokines has been modest with some notable exceptions. This review aims to describe current approaches toward targeting Signal 3 in clinical GVHD, and to highlight emerging studies in immune cell biology that may be harnessed for better clinical translation.